Marketing to rural consumers : understanding and tapping the rural market potential - Velayudhan, Sanal Kumar, 1955-; Sridhar, Guda.; Indian Institute of Management, Khozhikode (New Delhi : Excel Books, 2009)
Contributed articles presented at the conference on Marketing to Rural Consumers--Understanding and Tapping the Marketing Potential, held at IIM, Kozhikode in April 2008.
Includes statistical tables.
Includes bibliographical references.
Keywords: Farm produce -- India -- Marketing -- Congresses; Farmers as consumers -- India -- Congresses; Rural development -- India -- Congresses